The Impact of Art Education on the Upbringing and Beliefs of School Students - Katea, Dr.Ahmed Hussein; Swzan Naji Faisal (Thi Qar Arts Journal, 2025)
This research focuses on the impact of art education on school students’ beliefs, their experiences with learning the arts, and their perceptions of how it influences their academic achievement and goals. Specifically, the study addresses academic performance, student aspirations, awareness, and beliefs. It also reviews educational outcomes and policy issues as they relate to the future of art education. The research includes students’ beliefs regarding the importance of art education and its effect on academic achievement, aiming to enhance the credibility of the study. Based on current research that utilizes students’ own beliefs, the researcher presents a new perspective on the value of art education. The significance of the study lies in evaluating whether art education has an impact on students’ academic lives. To justify the inclusion of art education in school curricula, educators must demonstrate that such studies are an integral part of a comprehensive educational plan. Increasingly, art teachers are required to justify their professional roles based on whether their disciplines can contribute to improving performance in mathematics, reading, and other academic areas. The objective of the research is to examine how students perceive their personal experiences with art education and their views on its influence on their academic achievement and goals. Definition of Art Education: Art education is defined as the type of education that relies on the use of various artistic activities in the fields of fine or applied arts, benefiting from various modern human sciences, as affirmed by Al-Shahin (2011).